Beyond single references: pangenome graphs and the future of genomic medicine - Nyaga, Denis M.; Zaied, Roan E.; Silander, Olin K.; Black, Michael A.; O’Sullivan, Justin M. (Frontiers in Genetics, 2025)
Genomic medicine relies on single reference genomes that miss crucial genetic diversity, creating diagnostic gaps that disproportionately affect underrepresented populations. Pangenome graphs, collections of diverse genomes represented as interconnected genetic paths, offer a powerful alternative to the standard reference genome approach. Pangenome-based approaches capture the spectrum of human variation, dramatically improving how we detect complex structural variants, reconstruct haplotypes, and reduce bias in genetic studies. Projects like the Human Pangenome Reference Consortium have identified hundreds of megabases of missing genetic diversity, leading to remarkable improvements in variant detection across different populations. Yet, as pangenomes grow larger and computationally complex, they become more challenging to interpret clinically, creating a trade-off between comprehensiveness and usability. This review discusses the technical and conceptual advances enabling clinical applications of pangenomes in rare disease diagnosis. Realizing the future potential of pangenome graphs in genomic medicine will require innovative implementation strategies, thorough clinical testing, and user-friendly approaches.